Optimizing the Use of Geogebra on Students' Communication Skills in Mathematics Learning - Faizah Tasya Nabila; Lukman El-Hakim; Tian Abdul Aziz (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Mathematical communication skills are essential skills that connect students understanding of concepts with the ability to express ideas systematically. This study aims to explain the optimization of the use of Geogebra in improving students mathematical communication skills in mathematics learning. The research method used is a systematic literature review (SLR) of 10 articles published in the 2021-2025 range. The literature search strategy is carried out through the Google Scholar, Research Date, and Publish or Perish databases. The results of the analysis show that the use of Geogebra as a learning medium is effective in improving students mathematical communication skills, both verbally and in writing. Geogebra helps students to visualize abstract concepts, encourage interaction in the classroom, and increase interest in learning through dynamic mathematical objects. It is concluded that the integration of Geogebra in the mathematics learning process has a significant impact on students ability to convey mathematical ideas, both verbally and non-verbally.